Lithuanians on the jubilee of the 125th birth anniversary of the great linguist Jan Szczepan Otrębski - Marcinkiewicz, Józef (Lingua Posnaniensis, 2016)
This article draws attention to the jubilee scientific conference which was held on 28th November 2014 in Vilnius, in the Parliament of the Republic of Lithuania, on the occasion of the 125th birth anniversary of the great Polish linguist Jan Szczepan Otrębski. A one-day seminar in Vilnius was attended by Lithuanian and Polish linguists, as well as politicians who opened the conference, thus emphasizing importance and significance of this event. During the conference nine interesting papers were read out about the life and work of Jan Sz. Otrębski, a linguist who devoted a large part of his life to research of the Lithuanian language. In general, the papers highlighted inter alia the genius of this scholar and his great contribution to the study of both the Lithuanian language as well as the other Indo-European languages. In other words, let background anniversary be a good opportunity to recall the figure of this great scholar.